Early signs of impaired renal function due to low grade subchronic lead intoxication in rats - Mohd Zairi, Nurul Huda; Hamzah, Hazilawati; Mohamed Mustapha, Noordin; Shaari, Mohd Rosly; Sithambaram, Shanmugavelu; Haron, Nursyuhada (2012)
Chronic high lead intoxication has been known to cause anaemia, nephropathy, gastrointestinal colic and neuropathy. Lead can be absorbed through the gastrointestinal and respiratory tract before being excreted through the kidneys. This study focuses on the early signs of impaired renal function in rats subjected to low grade lead toxicity through drinking water over a period of 12 weeks. Feed and water consumption were monitored during the course of the experiment, and the body weight were measured weekly. At the end of the stipulated time period, the rats were placed in individual metabolic cages for urine collection. Then, blood was collected via intracardiac puncture under general anaesthesia for haematology and plasma biochemistry evaluation. Finally, the rats were euthanized humanely to enable organ collection. Results showed no significant difference between body weight and water consumption, no clinical signs of anaemia, normal kidney parameters (blood urea nitrogen and creatinine) with significant increase (p<0.05) in blood potassium levels. Urinalysis revealed increased urine protein to creatinine ratio. There was also a significant decrease (p<0.05) in the kidney relative organ ratio between the group receiving 100 ppm lead (II) acetate daily and the control group. In conclusion, low grade subchronic lead intoxication indicates early signs of impaired renal function in rats which may lead to nephropathy.